2017
DOI: 10.1098/rspb.2017.0412
|View full text |Cite|
|
Sign up to set email alerts
|

Wind and rain are the primary climate factors driving changing phenology of an aerial insectivore

Abstract: While the ecological effects of climate change have been widely observed, most efforts to document these impacts in terrestrial systems have concentrated on the impacts of temperature. We used tree swallow () nest observations from two widely separated sites in central Alaska to examine the aspects of climate affecting breeding phenology at the northern extent of this species' range. We found that two measures of breeding phenology, annual lay and hatch dates, are more strongly predicted by windiness and preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…However, it is possible that the relevant timescale over which ambient temperature affects reproductive performance is longer than what was measured here. It is also possible that other unmeasured environmental factors influence reproductive success, alone or in combination with temperature (e.g., wind speed or precipitation: Ouyang et al, 2015;Irons et al, 2017). Finally, year effects could better predict reproductive success because, unlike ambient temperature, they incorporate other longer-term sources of variation, including the social environment, predator pressure, carry-over effects of conditions experienced during migration, or even global weather patterns that affect swallows on their non-breeding grounds.…”
Section: Reproductive Successmentioning
confidence: 99%
“…However, it is possible that the relevant timescale over which ambient temperature affects reproductive performance is longer than what was measured here. It is also possible that other unmeasured environmental factors influence reproductive success, alone or in combination with temperature (e.g., wind speed or precipitation: Ouyang et al, 2015;Irons et al, 2017). Finally, year effects could better predict reproductive success because, unlike ambient temperature, they incorporate other longer-term sources of variation, including the social environment, predator pressure, carry-over effects of conditions experienced during migration, or even global weather patterns that affect swallows on their non-breeding grounds.…”
Section: Reproductive Successmentioning
confidence: 99%
“…Only a few studies have linked higher wind speeds to reduced nestling growth, for example in nestling Blue Tits Cyanistes caeruleus (Mainwaring & Hartley 2016), Black-legged Kittiwakes Rissa tridactyla (Christensen-Dalsgaard et al 2018) and Eurasian Bittern (Kasprzykowski et al 2014). However, in contrast to rainfall and temperature, and despite growing evidence of its influence on reproductive traits (MĂžller 2013, Irons et al 2017, the impact of wind speed on chick growth has received less attention and is less well known (Mainwaring & Hartley 2016, Irons et al 2017. Similarly, the potential for interactive effects between different weather variables has rarely been considered (but see Dawson & Bortolotti 2000, Coe et al 2015, Mainwaring & Hartley 2016, de Zwaan et al 2019 for examples), despite the potential for synergistic or antagonistic relationships; for example, de Zwaan et al (2019) found that the delay in nestling development in Horned Lark Eremophila alpestris chicks, induced by low temperatures, was exacerbated by precipitation.…”
mentioning
confidence: 99%
“…, Irons et al. ), biogeochemical cycles (Ligeza and Smal ), water and atmosphere contamination (BauerovĂĄ et al. ), the availability of food source (Isaksson and Andersson , Chamberlain et al.…”
Section: Discussionmentioning
confidence: 99%
“…, Irons et al. ); and responses to anthropogenic changes in environments (e.g., light, noise, and air pollution; Dominoni et al. , Shannon et al.…”
Section: Introductionmentioning
confidence: 99%